African swine fever virus modulates the endoplasmic reticulum stress-ATF6-calcium axis to facilitate viral replication - Yanjin Wang; Jiaqi Li; Hongwei Cao; Lian-Feng Li; Jingwen Dai; Mengxiang Cao; Hao Deng; Dailang Zhong; Yuzi Luo; Yongfeng Li; Meilin Li; Dingkun Peng; et al. (Emerging Microbes and Infections)
African swine fever (ASF), caused by African swine fever virus (ASFV), is a devastating infectious disease of domestic pigs and wild boar, which threatens the global pig industry. Endoplasmic reticulum (ER) is a multifunctional signaling organelle in eukaryotic cells that is involved in protein synthesis, processing, posttranslational modification and quality control. As intracellular parasitic organisms, viruses have evolved several strategies to modulate ER functions to favor their life cycles. We have previously demonstrated that the differentially expressed genes associated with unfolded protein response (UPR), which represents a response to ER stress, are significantly enriched upon ASFV infection. However, the correlation between the ER stress or UPR and ASFV replication has not been illuminated yet. Here, we demonstrated that ASFV infection induces ER stress both in target cells and in vivo, and subsequently activates the activating transcription factor 6 (ATF6) branch of the UPR to facilitate viral replication. Mechanistically, ASFV infection disrupts intracellular calcium (Ca2+) homeostasis, while the ATF6 pathway facilitates ASFV replication by increasing the cytoplasmic Ca2+ level. More specifically, we demonstrated that ASFV infection triggers ER-dependent Ca2+ release via the inositol triphosphate receptor (IP3R) channel. Notably, we showed that the ASFV B117L protein plays crucial roles in ER stress and the downstream activation of the ATF6 branch, as well as the disruption of Ca2+ homeostasis. Taken together, our findings reveal for the first time that ASFV modulates the ER stress-ATF6-Ca2+ axis to facilitate viral replication, which provides novel insights into the development of antiviral strategies for ASFV.